AN OVERVIEW THE MEANING OF LIFE IN BREAST CANCER PATIENTS IN THE CITY OF LHOKSEUMAWE - Julistia, Rini; Muna, Zurratul; Astuti, Widi; Iramadhani, Dwi (Fakultas Psikologi, Universitas Islam Negeri (UIN) Ar Raniry Banda Aceh, 2022)
This study aims to describe the meaning of life in breast cancer patients in Lhokseumawe City. The study used descriptive quantitative methods and the sampling technique was simple random sampling. The results of this study indicate that patients with breast cancer in Lhokseumawe City have a high meaning of life. Individuals who have a high meaning of life are able to find the meaning of their lives, this can be seen from those who can think positively about what they are experiencing, can undergo all treatment processes with passion and enthusiasm, this can affect their own healing. Keywords: The Meaning of Life, Breast Cancer, Lhokseumawe